Extracorporeal membrane oxygenation after prosthetic valve replacement in a child with neonatal Marfan syndrome: a case report. Issue 9 (29th August 2022) - Wadia, Toranj; Desai, Ajay; Hoschtitzky, J Andreas; Naqvi, Nitha
Abstract: Background: Neonatal Marfan syndrome (nMFS), the most severe form of Marfan syndrome, is a rare condition that presents a clinical and treatment challenge. nMFS has high infant mortality related to progressive valvular dysfunction. Valve replacement in this setting improves long-term prognosis but carries high morbidity and mortality. Thus, sharing clinical experience in treating such patients is valuable. Case summary: A 2 year old with nMFS underwent tricuspid valve annuloplasty and prosthetic mitral valve replacement. Postoperative management was complicated by pulmonary hypertension, cardiogenic shock, and arrythmias. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) helped overcome these challenges but posed a high risk for prosthetic valve thrombosis (PVT). Despite decompression of the left atrium (LA) with an LA vent, the left ventricle (LV) was distended because of aortic regurgitation and no native cardiac output. We lowered the ECMO flow under echocardiographic guidance; used inodilators and pacing to encourage transmitral flow and reduce LV afterload. The patient completed a successful 6-day ECMO run with good end-organ perfusion. At last follow up, she was 6 years old, enjoying school, home-ventilated through the tracheostomy, and mobilizing with walking aids/wheelchair. Discussion: Valve replacement can improve life quality and expectancy for patients with nMFS. Lowering ECMO flow under echocardiography guidance till the aortic valve is seen to open; coupled with inodilators, pacing and adequate anticoagulation can be a safe way to deliver VA-ECMO for cardiogenic shock after prosthetic valve replacement. Further research is needed to show if this strategy prevents prosthetic valve thrombosis and provides sufficient haemodynamic support and myocardial rest.